Evidence of the association of begomovirus and its betasatellite with the yellow vein disease of an ornamental plant Calendula officinalis (pot marigold) in Rajasthan, India: Molecular, Sequence and Recombination analysis - Marwal, Avinash; Sahu, Anurag Kumar; Gaur, Rajarshi Kumar (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Begomoviruses are major threats for various crops species throughout the globe, particularly in tropical and sub-tropical regions. Mutation, pseudorecombination and recombination are driving forces for the emergence and evolution of new begomoviruses. In light to that ornamental plants act as an alternate host of begomoviruses and its associated satellite molecules in the absence of main crop. Leaf yellow vein disease of Calendula officinalis plants was observed in Lakshmangarh city of Rajasthan province of India. Samples of Calendula officinalis leaves were collected from the gardens. An expected product of 550 bp in size was amplified from extracts of symptomatic leaf samples with universal primers on the coat protein region of begomovirus. Moreover, betasatellite were also detected using betasatellite specific universal primers. The presence of begomoviruses was also confirmed by Dot blot hybridization using cloned DNA-A probe of Papaya leaf curl virus. We have identified and characterized the begomovirus and its associated betasatellite through molecular, sequence and recombination analysis. The betasatellite is identified as a new recombinant species, sharing nucleotide identity with other isolates reported from China, Pakistan, Bangladesh and Taiwan. The present study also suggests that the exchange of betasatellites with other begomoviruses would create a new disease complex posing a serious threat to agriculture crops and horticulture ornamental plants production.